Corrosion Of The Gas Pipelines Of The Field Medvezhiye In The Different Landscape Types - Michael A. Velikotskij; Vadim P. Marakhtanov (Geography, Environment, Sustainability, 2020)
A forecast of the corrosion activity within different landscapes of the cryolithozone is poorly studied previously. This study represent a close correlation between the proportion of corroded sections of the gas pipeline route of the gas field Medvezhye (the North of Western Siberia, Russia) and the deviation of the redox potential of soils (ΔEh) depending on the specific landscape types (tract groups). Our study revealed that the maximum value of the standard deviation of the redox potential (ΔEh) predetermines the maximum currents of the differential pairs aeration of soils that activate electrochemical corrosion processes in pipelines. The value of ΔEh is proposed to use as the main indicator of the activity of corrosion of the landscape types in the permafrost region.